Prognostic value of global plaque volume calculated from the 3D reconstruction of the coronary tree in patients without significant coronary artery disease. A multicenter study - Carlos Cortés; Julio Ruiz-Ruiz; Fernando Rivero; Ramón López-Palop; Octavio Jiménez; Alfonso Freites; Luis R. Gonçalves-Ramírez; María Rosario Ortas Nadal; Sara Blasco; Mario García-Gómez; Clara Fernández; Luca Scorpiglione; et al. (REC: Interventional Cardiology (English Ed.))
ABSTRACT Introduction and objectives: The use of coronary physiology is essential to guide revascularization in patients with stable coronary artery disease. However, some patients without significant angiographic coronary artery disease will experience cardiovascular events at the follow-up. This study aims to determine the prognostic value of the global plaque volume (GPV) in patients with stable coronary artery disease without functionally significant lesions at a 5-year follow-up. Methods: We conducted a multicenter, observational, and retrospective cohort study with a 5-year follow-up. A total of 277 patients without significant coronary artery disease treated with coronary angiography in 2015 due to suspected stable coronary artery disease were included in the study. The 3 coronary territories were assessed using quantitative flow ratio, calculating the GPV by determining the difference between the luminal volume and the vessel theoretical reference volume. Results: The mean GPV was 170.5 mm3. A total of 116 patients (42.7%) experienced major adverse cardiovascular events (MACE) at the follow-up, including cardiac death (11%), myocardial infarction (2.6%), and unexpected hospital admissions (38.1%). Patients with MACE had a significantly higher GPV (231.6 mm3 vs 111.8 mm3; P < .001). The optimal GPV cut-off point for predicting events was 44 mm3. Furthermore, in the multivariate analysis conducted, plaque volume, diabetes, hypertension, age, dyslipidemia, smoking, age, and GPV > 44 mm3 turned out to be independent predictors of MACE. Conclusions: GPV, calculated from the three-dimensional reconstruction of the coronary tree, is an independent predictor of events in patients with stable coronary artery disease without significant lesions. A GPV > 44 mm3 is an optimal cut-off point for predicting events.